Optimalisasi Pemanfaatan Limbah Sekam Padi Untuk Mendukung Sektor Pertanian di Desa Belading, Kec. Sabak Auh, Kab. Siak - Y, Yasir; A, Aryanto; Hilal, Octiara Irani; Alexandro, Gilberto; Putri, Nadia Rahma; Jannah, Safinatul; Putri, Syahanaya; Mutaqin, Fathoni; Rahmanda, Frendy; Amelia, Rosa; Azzahra, Annisa (Yayasan Daarul Huda Kruengmane, 2024)
Located in Sabak Auh sub-district, Siak Regency, Belading Village is a region renowned for its highly productive rice farming. The village's inhabitants hail from diverse backgrounds, with the Javanese community constituting the majority, fostering a strong tradition of consensus-based decision-making. The practices of mutual cooperation and other local wisdom have been deeply ingrained in the community since the village's inception, effectively preventing conflicts among different groups. Recognizing the significant potential of rice husk waste, there is a pressing need to empower the community to utilize this resource, such as by producing charcoal briquettes or organic fertilizers. However, the abundance of rice husk produced has often been underutilized. Rice husk, the outer layer protecting the rice grain, is commonly regarded as agricultural waste with limited value. Therefore, this initiative aims to empower the village community to harness rice husk as a valuable raw material that is both economically viable and environmentally friendly